Frequency of Hypoglycemia in Insulin-Treated Patients of Type 2 Diabetes Mellitus - Sumayya Shabbir, Hafiz Muhammad Umar Masood, Raja Sheraz Ullah Khan, Zaina Jabeen, Asif Islam, Muhammad Furqan Saeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Our study was designed to explore the frequency of hypoglycemia events in type 2 diabetic patients. We further aimed to correlate the hypoglycemia events with treatment regimes and diabetes duration. Place and Duration: Mayo Hospital Endocrine Outpatient Department. From 1-04-2022 to 30-06-2022. Study type: Clinical based study Methodology: We used the already tested questionnaire from the American Diabetes Association and The Endocrine Society to collect the relevant information. The questionnaire was translated into the local language to facilitate the interview. Copies of the questionnaire were distributed to 1000 patients at the study site. The questionnaire was based on socio-demographic and clinical information including gender, age, duration of diabetes, treatment, frequency of hypoglycemia events, and symptoms. Chi-square was used to analyze the association of risk factors. While odd ratios were also computed at a 95% confidence interval. P-value <0.05 was considered for statistical significance. Results: Total of 360 cases T2DM had hypoglycemic events with a prevalence of 36%. The mean age of patients was reported as 51 years. A total of 200 cases were found in the mentioned age group with a 55.56% prevalence. Elderly age patients were also the secondary target of hypoglycemia with a prevalence ratio of 27.78%. Out of these 360 patients, 320 (86.11%) had mild to moderate hypoglycemia with symptoms of eye tarnishing, tremors, numbness of the tongue, and drowsiness while 15% of cases lost their consciousness and were categorized as severe events of hypoglycemia. Conclusion: The study concluded on a note that insulin-treated patients should be aware of the hypoglycemia events because in these cases the risk is comparatively high than in others. Keywords: Diabetes mellitus, Insulin, Hypoglycemia